2016
DOI: 10.1016/j.aquaculture.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of water salinity effects on the sea lice Lepeophtheirus salmonis found on farmed Atlantic salmon in Muchalat Inlet, British Columbia, Canada

Abstract: The sea louse Lepeophtheirus salmonis is a major ectoparasite of both farmed and wild salmonids that causes substantial economic losses to the salmon industry worldwide. However, in British Columbia (BC) sea lice do not typically represent a significant health threat to farmed salmon. Sea lice patterns on Atlantic salmon farms in BC are not fully understood, but it is believed they are highly influenced by sea water salinity levels, which vary dramatically over the year. The objective of this investigation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Weekly water temperature and salinity during the follow‐up period were included in the model building process, as these factors have been described as strong modulators of C. rogercresseyi 's life cycle in experimental (Bravo, Pozo & Silva, ; González & Carvajal, ) and observational settings (Kristoffersen et al., ; Yatabe, Arriagada, Hamilton‐West & Urcelay, ). Previous research into L. salmonis has found that salinity probably reduces the survival rates of the larval and sessile stages of L. salmonis (Arriagada, Vanderstichel, Stryhn, Milligan & Revie, ; Samsing et al., ; Tucker, Sommerville & Wootten, ). Consequently, in order to tackle these lice stages, we evaluated the effect of water salinity 1 and 2 weeks prior the sea lice assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Weekly water temperature and salinity during the follow‐up period were included in the model building process, as these factors have been described as strong modulators of C. rogercresseyi 's life cycle in experimental (Bravo, Pozo & Silva, ; González & Carvajal, ) and observational settings (Kristoffersen et al., ; Yatabe, Arriagada, Hamilton‐West & Urcelay, ). Previous research into L. salmonis has found that salinity probably reduces the survival rates of the larval and sessile stages of L. salmonis (Arriagada, Vanderstichel, Stryhn, Milligan & Revie, ; Samsing et al., ; Tucker, Sommerville & Wootten, ). Consequently, in order to tackle these lice stages, we evaluated the effect of water salinity 1 and 2 weeks prior the sea lice assessment.…”
Section: Methodsmentioning
confidence: 99%
“…Salinity and temperature measurements were taken at wild sites using either YSI R 85 or YSI R 6-series multi-parametric sondes (YSI Incorporated, www.ysi.com). At farm sites, these were measured using an RHS-10ATC refractometer (Huake Instrument Co, Guangdong, China), and an OxyGuard Handy Polaris portable meter (Arriagada et al, 2016). Farm measurements were taken at the surface (<20 cm) and at depths of 1, 5, 10, and 15 m, while wild site measurements were taken at the surface (<20 cm) and at depths of 1 and 5 m. Water temperature and salinity were recorded up to two decimal points in degrees Celsius and parts per thousand (ppt) respectively, daily, for the whole year, for each salmon farm site (when sites were active), at the same location and at approximately the same time each morning.…”
Section: In Situ Datamentioning
confidence: 99%
“…The effects of salinity on the development of L. salmonis and local infestation levels in regions of BC for this parasite have been established 30 , 40 . In line with our study objective, to account for the potential confounding effects of salinity and temperature on the relationship between the overall load of lice from the farms and the prevalence of infestation on wild fish, we included the month fixed-effects as well as the year random effects in our final models.…”
Section: Discussionmentioning
confidence: 99%
“…Because the farming activity was limited to only one farm between 2004 and 2007, we initiated our study with the 2007 data. More details on sampling and lice counting procedures have been presented elsewhere 30 . For our statistical analyses, the data were aggregated at the farm level and each analytical unit was defined as a unique combination of farm-year-month.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation